Evaluation of periostin levels in gingival crevicular fluid and peri-implant sulcus fluid in patients with periodontal and peri-implanter disease: A cross-sectional study - Uzunkaya, Meral; Gundogar, Hasan (Annals of Medical Research, 2021)
Aim: Periodontal and peri-implanter diseases are chronic, infectious and inflammatory diseases that manifest as a result of the relationship between their primary etiologic factor, i.e. microbial dental plaque, and the host defense system. Periostin is a protein that has been shown to play a functional role in wound repair, cardiovascular diseases, bone and tooth regeneration and tooth morphogenesis. In this study, the aim was to understand the role of periostin in periodontal (Gingivitis and Periodontitis) and peri-implant (Peri-implant mucositis and Peri-implantitis) disease.Material and Methods: Forty-two subjects were enrolled in this cross-sectional study. In the clinical measurements, PPD, GI and PI values were measured from the implants and natural teeth. Peri-implant sulcus and gingival crevicular fluids were collected from the patients using paper strips. Periostin levels were measured using ELISA. All parameter was statistically tested by using third party software (SPSS v24.)Results: In terms of PPD, there was a statistically significant difference between the gingivitis-periodontitis, gingivitis-peri-implantitis, peri-implant mucositis-periodontitis and peri-implant mucositis-peri-implantitis groups. There was a statistically significant difference between the gingivitis-periodontitis, gingivitis-peri-implantitis and peri-implant mucositis-peri-implantitis groups in terms of GCF/PISF volume. Although there was no statistically significant difference between the groups in terms of the amount of GCF/PISF periostin, periostin values were higher in peri-implant mucositis and gingivitis samples as compared to the peri-implantitis and periodontitis groups.Conclusion: Clinical parameters are a valid diagnostic tool for peri-implanter disease; there is a need for multicenter studies to understand the inflammatory basis of peri-implanter diseases that are biochemically prospective.Keywords: Periodontitis; periostin; peri-implantitis; peri-implanter mucositis, gingivitis.
Keywords: Periodontitis; periostin; peri-implantitis; peri-implanter mucositis, gingivitis.